IA e criatividade de máquina na geração da ilusão suficiente em videogames - Fusaro, Alberto Cabral (2023)
Our investigation fits into a branch of Artificial Intelligence research, namely the Weak AIs subset, aiming to figure out the way that these AIs are applied in videogames development – we call it just “games”, referring to all games that run on any form of electronics platform. Our focus bears on how a set of AI agents, generating different illusions, whether of intelligence, affection, realism and so on, participate in an illusory system in balance with each game element in its fair measure to form a sufficient illusion, an effect resulting from the triadic interaction between the player, the gameplay and the game, in which a virtual space of immersive reality is formed, so the experience of playing and the resulting emotions are real